2019
DOI: 10.1088/1361-6501/ab04ea
|View full text |Cite
|
Sign up to set email alerts
|

Imaging phosphor thermometry from T  =  20 °C to 450 °C using the time-domain intensity ratio technique

Abstract: We present an imaging phosphor thermometry system using the time-domain intensity ratio technique and demonstrate surface temperature measurements that are traceable to ITS-90 with a calibration Standard uncertainty of 0.5 °C, over the range 20 °C to 450 °C. The thermographic phosphor used was Mg 4 FGeO 6 :Mn. Typically, imaging phosphor thermometry systems make use of the intensity ratio of the phosphor emission in two discrete wavelength bands, measured simultaneously using two cameras viewing the same surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…The maximum stress prior to hardening is,  = 12.3 MPa; accordingly, creep tests were carried out in the temperature range; 1300C to 1240C for a range of stresses up to a maximum value of 12 MPa. In the cooling experiments for a cooling rate of 0.1 C s-1, the time duration for a decrease in temperature by 10 C is 100 s; therefore, creep at any stress was conducted for a maximum time interval of 100 s. This is in sharp contrast to that reported in other studies [23]. Table 6, the strain induced is underlined, as in Table 5 for flow stress.…”
Section: Creepmentioning
confidence: 98%
See 1 more Smart Citation
“…The maximum stress prior to hardening is,  = 12.3 MPa; accordingly, creep tests were carried out in the temperature range; 1300C to 1240C for a range of stresses up to a maximum value of 12 MPa. In the cooling experiments for a cooling rate of 0.1 C s-1, the time duration for a decrease in temperature by 10 C is 100 s; therefore, creep at any stress was conducted for a maximum time interval of 100 s. This is in sharp contrast to that reported in other studies [23]. Table 6, the strain induced is underlined, as in Table 5 for flow stress.…”
Section: Creepmentioning
confidence: 98%
“…Water-cooled grips are used to give a temperature gradient along the length of the sample [21,22]. Recent studies have confirmed that at a central temperature up to around 900C, the temperature distribution along the test-piece is parabolic [23,24]. Consequently, the temperature variation along the 3 mm gauge length for Ni-base alloys is typically 5C [25].…”
mentioning
confidence: 99%
“…Imaging luminescence thermometry can be implemented for both decay time and intensity ratio techniques. In our previous work [12] we presented an imaging system based on the decay time method, where three images are captured with a single camera at different times after extinction of the excitation light: 1) immediately following extinction, 2) a fixed time after extinction and 3) once all luminescence has ceased (background measurement). We refer the reader to the publication for full details.…”
Section: Imaging Luminescence Thermometrymentioning
confidence: 99%
“…Thermographic phosphors exhibit a change in their temporal or spectral luminescence properties during or following excitation with UV or near-UV light. For a comprehensive summary of phosphor thermometry, we refer the reader to the review articles [9][10][11], with details of our earlier work given in [12]. Here we confine ourselves to the basic principles of the two most common phosphor thermometry techniques: decay time and intensity ratio.…”
Section: Introductionmentioning
confidence: 99%
“…[14] However, slower measurements can also be performed by changing the excitation pulse-exposure delay between consecutive pulses. [15][16][17] Based on the time domain, this approach has the advantage of robustness against spectral DOI: 10.1002/adpr.202100139 Luminescence thermometers exhibiting ratiometric response in their emission spectrum are widely investigated but to obtain two-dimensional measurements, either the emission spectrum must be slowly scanned over the area of interest or the emission decomposed using two separate detector arrays with spectral filters.…”
Section: Introductionmentioning
confidence: 99%